SINTESIS 3,4-DIMETOKSIBENZIL ASETAT DAN METIL-(3,4- DIMETOKSIFENIL) ASETAT DARI VANILIN DENGAN METODE SONIKASI - , FIA NABILA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Synthesis of 3,4-dimethoxybenzyl acetate and methyl-(3,4-dimetoxy phenyl) acetate from vanillin have been carried out. Both esters have an activity as attractant fruit flies Dacus dorsalis and Dacus curcubitae. Synthesis of 3,4-dimethoxybenzyl alcohol was carried out via methylation of vanillin followed by reduction. Vanillin methylation with dimethyl carbonate (DMC) was performed under sonication. This reaction yielded 98,36% veratraldehyde. Veratraldehyde was then reduced at room temperature using NaBH4 with stirring and sonication methods, yielded 97,00 and 98,87% 3,4- dimethoxybenzyl alcohol, respectively. 3,4-Dimethoxybenzyl acetate was yielded 98.28% from esterification of 3,4-dimethoxybenzyl alcohol and acetic acid by the use of sulfuric acid as a catalyst with sonication. Methyl-(3,4-dimethoxyphenyl) acetate was produced via 4 concecutive reactions, i.e. 1) chlorination of 3,4-dimethoxybenzyl alcohol with SOCl2 yielded 77,75% 3,4-dimethoxybenzyl chloride, 2) nitrilization of 3,4- dimethoxybenzyl chloride with NaCN in acetone yielded 66,16% 3,4- dimethoxyphenyl acetonitrile, 3) the product was then hydrolyzed with HCl, yielded 89,28% 3,4-dimethoxybenzyl carboxylate and 4) esterification of 3,4- dimethoxybenzyl carboxylate using methanol and sulfuric acid as a catalyst by sonication, yielded 95.23% yellowish viscous liquid of methyl-(3,4- dimethoxyphenyl) acetate.